2004
DOI: 10.1002/pssb.200304296
|View full text |Cite
|
Sign up to set email alerts
|

CdZnTe and CdTe materials for X‐ray and gamma ray radiation detector applications

Abstract: PACS 71.55. Gs, 72.20.Jv, 72.80.Ey, 81.05.Dz, 85.60.Gz Good detection efficiency and high energy-resolution make Cadmium Zinc Telluride (CdZnTe) and Cadmium Telluride (CdTe) detectors attractive in many room temperature X-ray and gamma-ray detection applications such as medical and industrial imaging, industrial gauging and non-destructive testing, security and monitoring, nuclear safeguards and non-proliferation, and astrophysics. Advancement of the crystal growth and device fabrication technologies and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
231
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(239 citation statements)
references
References 22 publications
4
231
0
4
Order By: Relevance
“…[29][30][31][32] CdTe has a direct optical band gap of ∼ 1.5 eV with a high absorption coefficient. The conjugate gradient algorithm was used to optimize the structure.…”
Section: 2324mentioning
confidence: 99%
“…[29][30][31][32] CdTe has a direct optical band gap of ∼ 1.5 eV with a high absorption coefficient. The conjugate gradient algorithm was used to optimize the structure.…”
Section: 2324mentioning
confidence: 99%
“…1,2 Deep levels play a key role on the electrical and transport charge properties of CdTe, determining the final detector's performance. [3][4][5][6] For example, has been demonstrated that the presence of these recombination deep centers is the mainly reason of the polarization effect of detectors, leading to the collapse of their internal electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor radiation detectors are of considerable technological importance due to their increasing use in medical imaging, and industrial and transportation security applications [1,2]. To fabricate such a high-quality semiconductor-based radiation detector, high-quality and high-purity semiconductor single crystals are needed.…”
Section: Introductionmentioning
confidence: 99%